Enhancing Supply Chain Agility through Digital Tools: A Quantitative Study in Pharmaceutical Distribution - Degdo Suprayitno (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the last decade, the complexity of global markets and increasing uncertainty have required companies to adopt more agile supply chain models. This study aims to explore the impact of digital tools on supply chain smoothness at PT Enseval Putera Megatrading Tbk, a pharmaceutical distribution company in Indonesia. This study aims to analyze the extent to which the adoption of digital tools, such as ERP and IoT, can improve responsiveness, flexibility, and speed in the distribution process. This study uses a quantitative approach with a field survey design. Data were collected through questionnaires distributed to 100 respondents involved in distribution operations. Linear regression analysis was used to test the relationship between the use of digital tools and supply chain agility. The findings show that the use of digital tools has a positive and significant impact on supply chain agility. These results indicate that increasing the use of digital tools can improve a company's responsiveness and flexibility. This study provides strategic implications for distribution management, emphasizing the importance of investing in digital technologies to enhance supply chain agility. These findings contribute to the development of dynamic capabilities theory in the context of supply chain digitalization.